2019
DOI: 10.3233/wor-192856
|View full text |Cite
|
Sign up to set email alerts
|

“He’s worth the extra work”: The employment experiences of adults with ASD who use augmentative and alternative communication (AAC) as reported by adults with ASD, family members, and employers

Abstract: BACKGROUND: Employment is a key determinant in quality of life. However, less than 50% of adults with ASD are employed. OBJECTIVE: In order to better support community-based employment for persons with ASD who use augmentative and alternative communication (AAC), there is a need to better understand those situations in which successful outcomes have been achieved. METHOD: This study utilized a multiple case design to investigate the experiences of seven individuals with ASD who use AAC and are successfully emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Richards and colleagues (2019: 1912) concluded that most managers are “insufficiently literate” regarding neurodiversity and thus are likely to feel isolated and unsupported when tasked with managing a neurodivergent employee. Beyond having difficulties managing autistic employees on their own, research has revealed that managers have “found themselves in situations that required them to attempt to teach others about autism, even though they themselves had limited training in this area” (Richardson, McCoy, & McNaughton, 2019: 213).…”
Section: Discussionmentioning
confidence: 99%
“…Richards and colleagues (2019: 1912) concluded that most managers are “insufficiently literate” regarding neurodiversity and thus are likely to feel isolated and unsupported when tasked with managing a neurodivergent employee. Beyond having difficulties managing autistic employees on their own, research has revealed that managers have “found themselves in situations that required them to attempt to teach others about autism, even though they themselves had limited training in this area” (Richardson, McCoy, & McNaughton, 2019: 213).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, video VSDS may provide a useful approach to addressing a current area of identified need: integrated technology support for both communication and participation in employment settings for persons with ASD and CCN (Light, McNaughton, & Caron, 2018;Richardson et al, 2019). Although the O' Neill et al (2017) case study provided preliminary evidence of the usefulness of video VSDs for an adolescent with ASD, there is a clear need for experimentally controlled research with persons with ASD and CCN.…”
Section: Video Visual Scene Displaysmentioning
confidence: 99%
“…It has been estimated that the employment rates for individuals with CCN are even lower (less than 5%) than those for individuals with ASD McNaughton & Bryen, 2002). The use of augmentative and alternative communication (AAC), such as sign language, picture communication boards, and AAC apps on mobile technology, has been demonstrated to benefit persons with ASD (Foley & Staples, 2003;Ganz, Boles, Goodwyn, & Flores, 2014;Sigafoos et al, 2004); however, there is only a limited understanding of how AAC might be used to support persons with ASD and CCN in participating in the workplace (Richardson, McCoy, & McNaughton, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations